LaMnO3 perovskites via a facile nickel substitution strategy for boosting propane combustion performance. Issue 5 (1st April 2020) - Zhang, Chuanhui; Zeng, Kai; Wang, Chao; Liu, Xuehua; Wu, Guanglei; Wang, Zhong; Wang, Da
Abstract: The B-site substitution by other metals is a feasible and efficient strategy to modulate the physicochemical properties and catalytic behaviors of perovskite-type metal oxides. Herein, series of LaMn1- x Ni x O3 ( x  = 0, 0.1, 0.2 and 0.3) catalysts were prepared for catalytic combustion of propane. The maintenance of perovskite structures but the occurrence of lattice shrinkage was observed after nickel substitution. Superior redox properties (i.e. low-temperature reducibility and surface oxygen mobility), higher average oxidation states of manganese and surface oxygen abundance were identified to be the key factors for the remarkable activity improvement. LaMn0.9 Ni0.1 O3 presented reversible partial deactivation under water vapor or carbon monoxide-containing atmosphere due to the surface completive adsorption/oxidation phenomenon of various gaseous components. Kinetics investigation revealed the different reaction orders towards propane and oxygen over LaMn0.9 Ni0.1 O3 and LaMnO3, which was of strong reflection about the surface adsorption behaviors of reactants molecules.